2018
DOI: 10.3389/fpsyg.2018.01454
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Chinese Version of the Neuroticism Subscale of the NEO-PI

Abstract: Neuroticism is an important concept in psychology, self-report measures of neuroticism are important for both research and clinical practice. The neuroticism subscale of the Neuroticism-Extraversion-Openness Personality Inventory (NEO-PI) is a brief measure of neuroticism, and it was widely used in the world. This study was aimed to examine the psychometric properties of the Chinese version of the neuroticism subscale of the NEO-PI. A total of 5,494 undergraduates from three universities and 551 clinical patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In clinical samples, the strict equivalence was not supported. But the residual equivalence is the most strict equivalence limit and it is not necessary for most research (59). In summary, the results of this study confirmed that the Chinese RRS-10 has strong equivalence, indicating that the scale is effective and interpretable between gender groups.…”
Section: Discussionsupporting
confidence: 59%
“…In clinical samples, the strict equivalence was not supported. But the residual equivalence is the most strict equivalence limit and it is not necessary for most research (59). In summary, the results of this study confirmed that the Chinese RRS-10 has strong equivalence, indicating that the scale is effective and interpretable between gender groups.…”
Section: Discussionsupporting
confidence: 59%
“…Researchers have also examined the structure of the facet scales and extended this research into different populations. Testing the N facet scales in both clinical and nonclinical samples in mainland China, Xi et al (2018) found support for the original six-facet structure, with acceptable internal consistency and test-retest reliability. Using differential item functioning, Dai et al (2010) assessed the measurement invariance of the C facet scales in a U.S. sample and a mainland Chinese sample.…”
Section: Neo Research In Chinese Communitiesmentioning
confidence: 81%
“…The neuroticism subscale of the short version of the Big Five Personality scale, compiled by Costa et al [ 42 ], was adopted, which has been proved to have good reliability and validity in Chinese samples [ 43 ]. The scale uses 12 items, each one rated on a five-point scale.…”
Section: Methodsmentioning
confidence: 99%